Institute of Property and its Role in Realization of the Constitutional Framework of the Economic System of the Russian Federation - ALEKSIKOVA, Olga E.; MELNIK, Evgenia A.; PONOMAREVA, Yulia Y.; FOMINA, Mariia G.; SHCHEGOLEVA, Natalia A. (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505/jarle.v9 3(33).03, 2018)
In Russia, the problems of economic relations have always been among the central ones and have not lost their topicality. At the modern stage of development of the Russian Federation, a new – as to content, goals, and tasks – economic system is established, based on such constitutional principles as the unified economic space, support for fair competition, freedom of economic activity, and equal protection of all property forms. Scientific consideration of the legal nature and the notion of institute of property and its role in realization of the economic system of Russia is a significant task of the legal science.